PRINT CAPTURE RT-PCR TO DETECT GROUNDNUT BUD NECROSIS VIRUS CAUSE OF POTATO STEM NECROSIS DISEASE - Kaushal, Nimisha; Bhatnagar, A; Tiwari, Jagesh K.; Kumar, Deep; Kaundal, Priyanka; pandey, S K; Garg, I D (Potato Journal, 2013)
potato stem necrosis disease (PSND) is a problem in early planted potato crop, caused by groundnut bud necrosis virus (GBNV) vectored by thrips. diagnosis of GBNV in leaf samples and thrips tissues was carried out using a simple technique i.e. print capture reverse transcriptase polymerase chain reaction (PC-RT-PCR). This technique involves spotting of samples onto NCMS, eluting viral rna from the NCM in sterile distilled water (20 Âµl) at 95Â°c for 10 min, CDNA synthesis followed by PCR amplification and analysis of the PCR product on 1.6% agarose gel. GBNV was detected in the leaf samples and thrips tissues which amplify at 800 bp in the first planted crop while, samples from later planted potato crop did not correspond to the results like the first crop.